Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Melalui Model PBL dan Pendekatan TaRL SMA Negeri 2 Medan - Nurmila Hidayana; Pandu Prabowo Warsodirejo; Hasda Tanty (Mathematics Education Study Program, 2025)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential so that they have religious spiritual strength, self-control, personality, intelligence, noble morals, and the skills needed by themselves, society, nation and state. . Mathematics as one of the main pillars in education has a very important role in developing logical thinking and problem solving abilities. One learning that is thought to be able to improve students' ability to solve mathematical problems is problem-based learning such as Problem Based Learning (PBL) . The model is in line with the approach Teaching at the Right Level (TaRL) where there is differentiation when conducting group discussions using this approach, students are expected to more easily understand mathematical concepts and be able to apply them in problem solving so that students' mathematical problem solving abilities can increase. The aim of this research is whether the PBL model and TaRL approach can improve students' mathematical problem solving abilities. The research method used was classroom action research (PTK) which was carried out at SMA Negeri 2 Medan involving 36 students in class X-11 as research subjects. Based on the research results, it can be concluded that the PBL model and TaRL approach can improve students' mathematical problem solving abilities as seen from the percentage in Cycle I 44% and Cycle II 81%.